Inclusive leadership: Realizing positive outcomes through belongingness and being valued for uniqueness - Randel, Amy E.; Galvin, Benjamin M.; Shore, Lynn M.; Ehrhart, Karen Holcombe; Chung, Beth G.; Dean, Michelle A.; Kedharnath, Uma (Human resource management review, 2018)
We introduce a theoretically-grounded conceptualization of inclusive leadership and present a framework for understanding factors that contribute to and follow from inclusive leadership within work groups. We conceptualize inclusive leadership as a set of positive leader behaviors that facilitate group members perceiving belongingness in the work group while maintaining their uniqueness within the group as they fully contribute to group processes and outcomes. We propose that leader pro-diversity beliefs, humility, and cognitive complexity increase the propensity of inclusive leader behaviors. We identify five categories of inclusive leadership behaviors that facilitate group members' perceptions of inclusion, which in turn lead to member work group identification, psychological empowerment, and behavioral outcomes (creativity, job performance, and reduced turnover) in the pursuit of group goals. This framework provides theoretical grounding for the construct of inclusive leadership while advancing our understanding of how leaders can increase diverse work group effectiveness. •Pro-diversity beliefs and humility are proposed antecedents of leader inclusion.•Inclusive leadership is posited to involve five categories of behaviors.•Encouraging belonging and valuing for uniqueness are proposed to foster inclusion.•Inclusion perceptions are posited to foster group identification and empowerment.•Creativity is proposed as one outcome resulting from inclusive leadership.